Synergistic nano-vaccine strategy for comprehensive activation of adaptive and innate immunity against Staphylococcus aureus infection - Xi, Jiayue; Cui, Minxuan; Shi, Zhuoyue; Wan, Zhuo; Hou, Yufei; Sun, Nan; Li, Muqiong; Ma, Zhengjun; Zhu, Yupu; He, Xin; Yang, Qian; Shi, Zhuojun; et al. (Frontiers in Immunology, 2025)
For decades, Staphylococcus aureus (S. aureus) vaccine development prioritized humoral immunity, heavily relying on recombinant protein antigens adjuvanted with aluminum (Alum), particularly in multivalent formulations. However, clinical limitations of Alum and the pressing challenge of antibiotic resistance have necessitated strategies that engage comprehensive adaptive and innate immunity. Addressing this critical gap, we engineered a biomimetic nanovaccine platform. Building on our previous finding that PLGA nanoparticles of specific stiffness effectively activate both humoral and cellular immunity, we conjugated two key ESAT-6-like virulence antigens, rEsxA and rEsxB, to stiffness-tuned PLGA nanoparticles with 25% PEG conjugation (25% NPs), designed to mimic staphylococcal capsule rigidity. We evaluated the biosafety and efficacy, both in vitro and in vivo, of single nano-vaccines (25% NPs-rEsxA or 25% NPs-rEsxB) and a vaccine combination (25% NPs-rEsxA+25% NPs-rEsxB). The combined vaccine demonstrated exceptional immunogenicity, significantly elevating antigen-specific IgG titers and inducing robust Th1/Th17-polarized cellular immunity, evidenced by 4.4-fold increases in IFN-γ and IL-17A secretion compared to Alum-adjuvanted controls. Crucially, this coordinated activation of adaptive and innate immunity conferred unprecedented protective efficacy: achieving 100% survival against a standard lethal dose (LD100) of S. aureus and 80% survival against a doubled lethal challenge (2×LD100)-outcomes substantially surpassing all controls. Our findings establish that dual-antigen targeting combined with biomimetic nanoadjuvants overcomes the limitations of traditional vaccines by holistically activating humoral, cellular, and innate immune responses, providing a potent strategy against invasive S. aureus infections, particularly relevant for combating drug-resistant strains.